2020
DOI: 10.4000/rdst.3208
|View full text |Cite
|
Sign up to set email alerts
|

Initiatives d´activisme en formation initiale de professeurs : préparer à l´action et à la transformation

Abstract: L'action collective raisonnée, connue sous le nom d'activisme, orientée vers la résolution de problèmes de la société, offre des possibilités d'apprentissage tout au long de la vie et permet aux étudiants de développer des connaissances du domaine de la science et de la technologie. Dans une société où les découvertes scientifiques et les progrès technologiques sont constants, les potentialités de cette approche sont également reconnues dans la formation de citoyens responsables, capables d'agir et de résoudre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The affirmations of the participants made it possible to understand that the experience of the project could motivate these future professionals to include practices that are oriented towards sustainability and organised according to this pedagogical approach in their future professional activity. These data support the data obtained in previous studies conducted by Linhares and Reis [22], which showed the importance of an effective integration of practices oriented to education for environmental citizenship and for action in the initial training of education professionals to enable them to implement these practices later in their own contexts of intervention.…”
Section: Evaluation Of the Education For Environmental Citizenship Pe...supporting
confidence: 90%
See 3 more Smart Citations
“…The affirmations of the participants made it possible to understand that the experience of the project could motivate these future professionals to include practices that are oriented towards sustainability and organised according to this pedagogical approach in their future professional activity. These data support the data obtained in previous studies conducted by Linhares and Reis [22], which showed the importance of an effective integration of practices oriented to education for environmental citizenship and for action in the initial training of education professionals to enable them to implement these practices later in their own contexts of intervention.…”
Section: Evaluation Of the Education For Environmental Citizenship Pe...supporting
confidence: 90%
“…In this same project, various studies conducted during pre-service teacher training made it possible to understand the potentialities, as well as some of the difficulties, which could arise with proposals oriented for action. In terms of potentialities, the important potentialities are those which focus on an understanding of the complexity of the environmental problems being analysed, as well as critical thought, communication and training for action [21,22]. The difficulties were essentially due to a lack of familiarity with the approaches, which were oriented for action in the community.…”
Section: Educating For Sustainability Through Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of interactivity requires interaction between the visitors within the exhibition and between the visitors and the objects that are being exhibited [39,40]; an interaction that exists even if the visitor is only thinking and reflecting on the stimulus from the object, not requiring any physical movement [41,42]. Several studies have suggested guidelines on how to develop socio-scientific based exhibitions, such as presenting an interesting narrative in order to raise visitors' curiosity and challenge and stimulate their participation [43][44][45][46].…”
Section: Climate Activism: Exhibitionsmentioning
confidence: 99%